Breastfeeding practices in mothers: a qualitative study - Nanis S. Marzuki; Elizabeth Yohmi; Eveline Nainggolan; Badriul Hegar; Hanifah Oswari; I Gusti Ayu Nyoman Partiwi (Indonesian Pediatric Society, 2014)
Background Despite the WHO and UNICEF recorrunendations, the well-known breastfeeding benefits, and the efforts to promote and support breastfeeding; exclusive breastfeeding by Indonesian mothers remains low and contributes to high infant mortality rates.Objective To elucidate the fac tors that influence mothers' choices for infant feedingMethods This qualitative study was conducted as part of a nationwide survey. The study included 36 in-depth interviews of mothers with infants aged 0-11 months, and health care professionals, including general practitioners, pediatricians, and midwives. This study was performed between 0 cto ber - November 2 0 l 0 in both rural and urban areas of 4 provinces in Indon esia.Results We found that most mothers intended to breastfeed and had positive perceptions of breastfeeding. However, mothers faced many challenges in the practice of exclusive and proper breastfeeding. Additionally, the perceived definition of exclusive breastfeeding varied among the participants, leading to n on-exclusive breastfeeding attitudes. The most frequent reasons for mothers to introduce additional milk formula or food were the perception of an inadequate milk supply, infant dissatisfaction or fu ssiness after feeding. Different perceptions were also demonstrated in different regions and the varying levels of socioeconomic status. Health care practitioners (HCPs) were the most reliable source for giving adequate information, but unfortunately, they were not easily accessible and provided inconsistent information. Consequently, closely-related family members were the major contributors of information to a mother'schoice of infant feeding; because they were easily accessible.Conclusion Factors influencing mothers in their breastfeeding practices are their basic knowledge, demographic and socioeconomic status, as well as the availability of support from closelyrelatedfamily members, friends, and HCPs.